DAMPAK STRATEGI KOMUNIKASI PEMBANGUNAN TERHADAP PARTISIPASI DAN PERUBAHAN PERILAKU MASYARAKAT - Anto Kurniawan; Ririn Puspita Tutiasri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Stunting remains one of the major public health issues that requires effective communication between healthcare workers and the community. Ngulungkulon Village, Trenggalek Regency, is one of the villages that has successfully reduced stunting rates through direct counseling as an implementation of development communication. This study aims to analyze the development communication strategies implemented by healthcare workers through direct counseling in stunting education in Ngulungkulon Village, Trenggalek Regency. The study employed a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. The informants consisted of healthcare workers, health cadres, and community members involved in counseling activities. Data were analyzed through data reduction, data presentation, and conclusion drawing. The study adopted Jan Servaes' participatory development communication theory and Onong Uchjana Effendy's communication strategy theory, which emphasizes audience identification, message formulation, media selection, and the role of communicators. The findings are expected to provide a comprehensive description of the implementation of development communication strategies in stunting education through direct counseling and indicate that communication tailored to community characteristics, supported by appropriate communication media, and implemented through a participatory approach can improve public understanding and awareness of stunting prevention. This study is expected to serve as a reference for village governments, healthcare workers, and other stakeholders in developing more effective health communication strategies.